WASTEWATER AS A SOURCE OF ENERGY IN MICROBIAL FUEL CELLS - Yagofarova , A.Y.; Kurmanbaev , A.A.; Berdimuratov , K.T.; Ahmetollaev , I.A. (Eurasian Journal of Applied Biotechnology, 2017)
We investigated the simultaneous production of electrical power and wastewater sludge recycling by microbial fuel cells (MFC). The constructed MFC were comprised of two chambers, each with an approximate volume of 100ml, which were connected by salt bridge or proton exchange membrane (PEM). The graphitic anode was placed in one chamber, which was filled with wastewater sludge from a sewage treatment plant of Astana or a medium with acetate and electrogenic strain; a graphite cathode was placed in the other chamber and filled with an electrolyte. Several prototypes were created and tested in our laboratory. The most important parameters such as voltage and amperage were measured during 9 days; the maximum values obtained were 0.6V and 0.7mA. Moreover, the power generated by the MFC made in our laboratory was 0.42mW. Glass wool was selected as the material for PEM. The electrogenic properties of the selected bacterial strains BacillusamylofaciensU15, EnterobacterPs7, and LactobacillusfermentumTB4 were studied. EnterobacterPs7 was more active than the others. The fuel cell blocks were designed to accommodate a voltage increase. Thus, the eight MFC were connected successively. The maximum voltage was 2.6V and amperage 30μA. The maximum power of the electric current was 78.0 μW.